2014
DOI: 10.1016/j.proeng.2014.12.495
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and Electrochemical Properties of La2NiO4+δ-Based Cathodes in Contact with Ce0.8Sm0.2O2-δ Electrolyte

Abstract: The current work focuses on the investigation of the structural and electrical properties of La2NiO4±δ, La1.7Sr0.3NiO4±δ and La1.7Ca0.3NiO4±δ layered perovskites and electrochemical performance of the cathodes on their base in contact with the Ce0.8Sm0.2O1.9 electrolyte with special attention given to the influence of the introduction of the sintering additives (CuO, Bi0.75Y0.25O1.5) into cathode layers on their in-plane and polarization resistances. Studies by the dc four-probe technique and impedance spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 13 publications
2
19
0
Order By: Relevance
“…reported that the electrochemical performance of (La 1− x Sr x ) 2 NiO 4+ δ ( x =0–0.2) electrodes applied on yttria‐stabilized zirconia solid electrolyte with a CGO10 buffer layer decreases progressively with increasing Sr content ( R η =0.41 Ω cm 2 for x =0 and 14.4 Ω cm 2 for x =0.2 at 700 °C) and attributed this to a decrease of both the bulk oxygen diffusion and surface exchange rates caused by Sr substitution. Pikalova et al . observed an increase of the polarization resistance of (La 1− x Sr x ) 2 NiO 4+ δ electrodes on SDC electrolyte from 0.73 ( x =0) to 17.7 Ω cm 2 ( x =0.15) at 700 °C and also attributed this to a decrease of oxygen overstoichiometry and, therefore, oxygen‐ion transport in the nickelate phase with Sr substitution.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…reported that the electrochemical performance of (La 1− x Sr x ) 2 NiO 4+ δ ( x =0–0.2) electrodes applied on yttria‐stabilized zirconia solid electrolyte with a CGO10 buffer layer decreases progressively with increasing Sr content ( R η =0.41 Ω cm 2 for x =0 and 14.4 Ω cm 2 for x =0.2 at 700 °C) and attributed this to a decrease of both the bulk oxygen diffusion and surface exchange rates caused by Sr substitution. Pikalova et al . observed an increase of the polarization resistance of (La 1− x Sr x ) 2 NiO 4+ δ electrodes on SDC electrolyte from 0.73 ( x =0) to 17.7 Ω cm 2 ( x =0.15) at 700 °C and also attributed this to a decrease of oxygen overstoichiometry and, therefore, oxygen‐ion transport in the nickelate phase with Sr substitution.…”
Section: Introductionmentioning
confidence: 98%
“…[46] On the contrary,G uan et al [52] reportedt hat the electrochemicalp erformance of (La 1Àx Sr x ) 2 NiO 4+ +d (x = 0-0.2) electrodes appliedo ny ttria-stabilized zirconia solid electrolyte with aC GO10b uffer layer decreases progressivelyw ith increasing Sr content (R h = 0.41 W cm 2 for x = 0a nd 14.4 W cm 2 for x = 0.2 at 700 8C) and attributed this to ad ecrease of both the bulk oxygen diffusion and surface exchange rates caused by Sr substitution. Pikalova et al [53] observed an increase of the polarization resistance of (La 1Àx Sr x ) 2 NiO 4+ +d electrodes on SDC electrolyte from 0.73 (x = 0) to 17.7 W cm 2 (x = 0.15) at 700 8Ca nd also attributed this to ad ecrease of oxygen overstoichiometry and, therefore, oxygen-iont ransport in the nickelate phase with Sr substitution. Ac orrelation between the concentration of mobile ionic charge carriers (interstitial oxygen or oxygen va-cancies) and the electrochemical activity of porous electrodes was reported also for other Ruddlesden-Popper nickelates including oxygen-overstoichiometric La 2 Ni 1Ày Cu y O 4+ +d and oxygen-deficient La 4 Ni 3 O 10Àd -basedp hases.…”
Section: Introductionmentioning
confidence: 99%
“…In general, acceptor-type Asite doping leads to a decrease in oxygen over-stoichiometry and an increase in electron hole transport due to partial oxidation of Ni 2+ to Ni 3+ [4]. The A-site substitution in the range of x = 0-0.4 in La 2− A NiO 4+ (A = Ca, Sr) drastically decreases oxygen-ion conductivity and slightly improves the surface exchange kinetics [6] resulting in inferior electrochemical properties of La 2− A NiO 4+ compared to the undoped La 2 NiO 4+ [9]. The B-site substitution with donor-type dopants, such as Fe or Co, qualitatively produces the opposite effect on the properties of La 2 NiO 4+ compared with that for the Ca/Sr doping [5].…”
Section: Introductionmentioning
confidence: 99%
“…The La‐rich side of the system ( x ≤ 0.5, 4 ± δ ≥ 4) was extensively studied and is well covered in the literature . These oxides were tested for a variety of catalytic, and electrochemical applications; the latter include electrocatalysts for the oxygen evolution reaction in alkaline solution, electrode materials for direct electrochemical reduction of NO, oxygen‐permeable membranes,, , anodes for direct methanol fuel cells,, and cathodes for solid oxide fuel cells …”
Section: Introductionmentioning
confidence: 99%